Efficacy of type‐5 phosphodiesterase inhibitors in the drug treatment of premature ejaculation: a systematic review - McMAHON, CHRIS G.; McMAHON, CHELSEA N.; LEOW, LIANG JOO; WINESTOCK, CHRISTOPHER G (BJU international, 2006)
The aim of this section is to produce shortened reviews for the reader, in a variety of subjects. Three of the four fulfil these criteria, covering the subject of imaging in paediatric urology, minimally invasive nephron‐sparing surgery, and the ever‐interesting and controversial subject of men’s health. The first review published in this issue is rather longer than usual and contains more references. It is my intention that occasionally we should publish such longer reviews, particularly as in this case when it is a systematic review of the literature, which would be somewhat difficult to shorten anyway. The question of premature ejaculation is of great general interest and this review investigates the efficacy of type‐5 phosphodiesterase inhibitors in the drug treatment of that condition. ABSTRACT This review examines the role of nitric oxide (NO) as a neurotransmitter involved in the central and peripheral control of ejaculation, the methods of phosphodiesterase type 5 inhibitor (PDE5I) drug treatment studies for premature ejaculation (PE), the adherence of methods to the contemporary consensus of ideal PE drug trial design, the impact of methods on treatment outcomes and the role of PDE5Is in the treatment of PE. NO/cGMP transduction is involved in both the central and peripheral control of emission, but evidence for a direct central or peripheral effect of PDE5Is on ejaculation is speculative. Thirteen of the 14 studies reviewed failed to fulfil the evidence‐based medicine criteria for ideal PE drug trial design. Limitations of the studies include inadequately defined study populations, the lack of a double‐blind placebo‐controlled study design, and the absence of consistent objective physiological measures or sensitive, validated outcome assessment instruments as study endpoints. The broad range of intravaginal ejaculatory latency time (IELT) fold‐increases reported with PDE5Is, on‐demand selective serotonin re‐uptake inhibitor (SSRI) drugs, and combined PDE5I/on‐demand SSRIs is testament to the unreliability of data and conclusions from methodologically flawed studies. The one study that fulfilled the evidence‐based medicine criteria of an ideal clinical trial design reported that treatment with sildenafil failed to significantly increase baseline IELT, supporting our conclusion that there is no convincing evidence to support any role for PDE5Is in the treatment of men with lifelong PE and normal erectile function. However, there is limited evidence to support a potential role for PDE5Is alone or combined with daily or on‐demand SSRIs in the treatment of acquired PE in men with comorbid erectile dysfunction. Further controlled studies adhering to the contemporary consensus of ideal clinical trial design are required to clarify the role of PDE5Is in this subgroup of men with acquired PE.